(−)-Epigallocatechin-3-Gallate Reduces Perfluorodecanoic Acid-Exacerbated Adiposity and Hepatic Lipid Accumulation in High-Fat Diet-Fed Male C57BL/6J Mice - Hong Xu; Xu Zhong; Taotao Wang; Shanshan Wu; Huanan Guan; Dongxu Wang (Molecules, 2023)
Perfluorodecanoic acid (PFDA), an enduring and harmful organic pollutant, is widely employed in diverse food-related sectors. Our previous studies have provided evidence that PFDA has the potential to facilitate obesity and hepatic fat accumulation induced by high-fat diet (HFD) intake. Epigallocatechin-3-gallate (EGCG), a polyphenol found in green tea, has been suggested to possess potential preventive effects against metabolic abnormalities and fatty liver. The purpose of this research was to investigate the effects of EGCG on PFDA-exacerbated adiposity and hepatic lipid accumulation in HFD-fed mice. The results showed that EGCG reduced body weight gain; tissue and organ weights; blood glucose, serum insulin, HOMA-IR, leptin, and lipid parameters; serum inflammatory cytokines (IL−1β, IL−18, IL−6, and TNF−α); and hepatic lipid accumulation in PFDA-exposed mice fed an HFD. Further work showed that EGCG improved liver function and glucose homeostasis in mice fed an HFD and co-exposed to PFDA. The elevated hepatic mRNA levels of SREBP-1 and associated lipogenic genes, NLRP3, and caspase−1 in PFDA-exposed mice fed an HFD were significantly decreased by EGCG. Our work provides evidence for the potential anti-obesity effect of EGCG on co-exposure to HFD and PFDA and may call for further research on the bioactivity of EGCG to attenuate the endocrine disruption effects of long-term exposure to pollutants.